(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
In the Bükk Mountains the Upper Permian is represented by the Nagyvisnyó Limestone, which contains very rich marine assemblages. It is overlain by the Gerennavár Limestone (uppermost Permian-Lower Triassic) which records the effects of the Permo-Triassic mass extinction with a dramatic decrease in diversity and abundance of fossils. The basal Gerennavár Limestone is represented by a clayey marl unit (basal beds) deposited in a quiet, low-energy marine environment below the storm wave-base, whose maximum thickness, about one meter, is recorded in the Bálvány-North section. From this locality a relatively diversified and abundant marine benthonic assemblage has been collected, and is here described. Bivalves are represented by: Bakevellia cf. ceratophaga (Schlotheim), ? Pterinopectinidae gen. et sp. indet., Eumorphotis lorigae sp. n., the most abundant species, Entolium piriformis (Liu) and Pernopecten latangulatus Yin. Brachiopods are less frequent, and the following four species have been identified: Spinomarginifera sp., Orthothetina ladina (Stache), Ombonia tirolensis (Stache) and Orbicoelia tschernyschewi (Likharew). An exact age of this fauna, based on conodonts, is not yet available, but the strong affinities with those of the lower Tesero Member (Dolomites) and the Lower Kathwai Member (Pakistan) suggest a latest Permian age (? Hindeodus praeparvus Zone). If so, the Bálvány-North section becomes one of the few in the world which records the last bioevents of the Palaeozoic.